Palatability of Cuscus (Spilocuscus maculatus) to the Combinations of Pellet Feed Based on Organic Value - Sinery, Anton; Manusawai, Jacob; Worabay, Meliza; Taran, Denisa; Sirami, Elieser (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Cuscus (Spilocuscus maculatus) in captivity that were given a dominant fruit diet needed additional feed from their natural habitat because of the higher nutritional potential and fiber components. This study aims to determine the palatability of cuscus to the feed based on organic value. An experimental method was used, consisting of 4 treatment groups: 100% banana (Musa paradisiaca) as control, 70% banana mixed with 30% matoa (Pometia pinnata) leaves, 70% banana mixed with 30% ironwood (Pongamia pinnata) leaves, and 70% banana mixed with 30% crickets (Gryllus bimaculatus). The results showed that banana was the most preferred feed ingredient, either alone or as a supplementary feed mixture. In terms of quantity, its mixture with matoa leaves had a higher consumption level than ironwood leaves and crickets. The consumption level of organic matter was higher in the treatment with 100% banana than in other treatments. This information will help support ex-situ and in-situ conservation programs formulated by the government and other parties, including the community. Keywords: cuscus, feed, organic matter, palatability, Spilocuscus maculatus